A Study on Consumers' Perception About the Importance of Payment Processing Efficiency in Online Retailing Environment - Subrahmanya Sastry .T, D. V. R.; Madhusudhana Rao, B. (Indian Journal of Marketing, 2017)
The Internet as a global medium is quickly gaining focus and attractiveness as the most revolutionary marketing tool. Online shopping for various consumers is being accepted as an alternative shopping mode rather than visiting the physical stores. Understanding how consumers make a decision to use their resources such as time, money, and effort for buying goods and services is very important for businesses to bring in appropriate marketing strategies. Studying consumer buying pattern and decision making is directly linked to customer playing three distinct roles of buyer, payer, and user. If the companies doing business in an online environment can analyze the factors affecting consumer decision making in online shopping and the relationship between these factors, then they can formulate effective marketing strategies to convert potential customers into active ones, while retaining existing e-customers. This study was conducted to identify the association of two primary independent attributes (gender and income group) related to payment processing efficiency with consumer shopping motives in an online shopping environment. It was found that gender and income group did not have any influence on payment processing efficiency in the online retail purchasing process. The outcome of this study suggested that pay on delivery feature is a very useful option for online buyers to choose online retail websites for their shopping needs. It was also found that online payment security is very important in the online retailing environment.